Study on the criteria for assessing skull-face correspondence in craniofacial superimposition. (November 2016) - Ibáñez, Oscar; Valsecchi, Andrea; Cavalli, Fabio; Huete, María Isabel; Campomanes-Alvarez, Blanca Rosario; Campomanes-Alvarez, Carmen; Vicente, Ricardo; Navega, David; Ross, Ann; Wilkinson, Caroline; Jankauskas, Rimantas; Imaizumi, Kazuhiko; et al.
Highlights: Quantitative data for discussion of recommended craniofacial assessment criteria. Standardize identification methods based on the observation of morphological patterns. MEPROCS partners agreed on a reduced set of assessment criteria. Abstract: Craniofacial superimposition has the potential to be used as an identification method when other traditional biological techniques are not applicable due to insufficient quality or absence of ante-mortem and post-mortem data. Despite having been used in many countries as a method of inclusion and exclusion for over a century it lacks standards. Thus, the purpose of this research is to provide forensic practitioners with standard criteria for analysing skull-face relationships. Thirty-seven experts from 16 different institutions participated in this study, which consisted of evaluating 65 criteria for assessing skull-face anatomical consistency on a sample of 24 different skull-face superimpositions. An unbiased statistical analysis established the most objective and discriminative criteria. Results did not show strong associations, however, important insights to address lack of standards were provided. In addition, a novel methodology for understanding and standardizing identification methods based on the observation of morphological patterns has been proposed.